Inovasi Pemanfaatan Ubi Jalar Ungu (Ipomoea batatas L.) dalam Pembuatan Es Krim bagi Ibu Rumah Tangga - Fahrullah, Fahrullah; Mokoolang, Susan; Gobel, Yusriyah Atikah; Mokoginta, Meity M. (Universitas Nusantara PGRI Kediri, 2022)
Purple sweet potato is not only fresh but can also be added to ice cream products. Diversification of ice cream can be done by adding purple sweet potato which is a traditional food that contains antioxidants and anthocyanins which are good for health. This community service aims to provide knowledge about the various benefits of purple sweet potato from a health aspect. This activity is carried out by means of lectures, discussions and training in product manufacturing. The results obtained are that the housewives of Lamahu village already know the good nutritional content of purple sweet potatoes and can make ice cream products that will train their abilities and can increase family income.